Biological imaging for individualized therapy in radiation oncology: part II medical and clinical aspects. (9th March 2018) - Gkika, Eleni; Oehlke, Oliver; Bunea, Hatice; Wiedenmann, Nicole; Adebahr, Sonja; Nestle, Ursula; Zamboglou, Constantinos; Kirste, Simon; Fennell, Jamina; Brunner, Thomas; Gainey, Mark; Baltas, Dimos; et al.
Positron emission tomography and multiparametric MRI provide crucial information concerning tumor extent and normal tissue anatomy. Moreover, they are able to visualize biological characteristics of the tumor, which can be considered in the radiation treatment planning and monitoring. In this review we discuss the impact of biological imaging positron emission tomography and multiparametric MRI for radiation oncology, based on the data of the literature and on the experience of our own institution in this field.